2014
DOI: 10.3389/fnhum.2014.00081
|View full text |Cite
|
Sign up to set email alerts
|

Changes in GABA and glutamate concentrations during memory tasks in patients with Parkinson’s disease undergoing DBS surgery

Abstract: Until now direct neurochemical measurements during memory tasks have not been accomplished in the human basal ganglia. It has been proposed, based on both functional imaging studies and psychometric testing in normal subjects and in patients with Parkinson’s disease (PD), that the basal ganglia is responsible for the performance of feedback-contingent implicit memory tasks. To measure neurotransmitters, we used in vivo microdialysis during deep brain stimulation (DBS) surgery. We show in the right subthalamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…A previous study demonstrated that high-frequency DBS induced dyskinesia by activating NMDAR subunit NR2B, while another study revealed that DBS with stimulation in the frequency range of 100–200 Hz maximally activated extrasynaptic NMDARs subunit NR2B [ 72 , 73 ]. Previous studies revealed that DBS not only reduced the concentration of glutamate, but also the expression of GABA, during cognitive testing [ 74 , 75 ]. High-frequency stimulation suppresses spontaneous neuronal firing, suggesting that the stimulus intensity may regulate the inhibitory interneurons [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that high-frequency DBS induced dyskinesia by activating NMDAR subunit NR2B, while another study revealed that DBS with stimulation in the frequency range of 100–200 Hz maximally activated extrasynaptic NMDARs subunit NR2B [ 72 , 73 ]. Previous studies revealed that DBS not only reduced the concentration of glutamate, but also the expression of GABA, during cognitive testing [ 74 , 75 ]. High-frequency stimulation suppresses spontaneous neuronal firing, suggesting that the stimulus intensity may regulate the inhibitory interneurons [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, either elevated BG GABA levels (24,25) or reduced left striatum GABA levels (26) have been reported in animal studies. Our study showed reduced GABA+ levels in a BG region, which includes the striatum.…”
Section: Discussionmentioning
confidence: 65%
“…In previous human studies, GABA levels in the striatum or putamen have been reported to be either reduced, 22 unaltered, 14 or elevated 13,23 in PD compared with healthy controls. Similarly, either elevated BG GABA levels 24,25 or reduced left striatum GABA levels 26 have been reported in animal studies. Our study showed reduced GABA 1 levels in a BG region, which includes the striatum.…”
Section: Discussionmentioning
confidence: 66%
“…It was demonstrated in hemiparkinsonian rats that 6-hydroxydopamine lesioning increased the levels of glutamate and gamma-amino butyric acid (GABA) in striatum and SNr, which could be normalized by chronic STN-DBS (Chassain et al, 2016 ). As glutamate and GABA are closely related to the memory function in PD patients (Buchanan et al, 2014 ), it suggests STN-DBS may influence the basal ganglia networks which are associated with cognitive functions. Meanwhile, since pedunculopontine tegmental nucleus (PPTg) acts as an interface between the basal ganglia and cerebellum, it has potentials to influence motor control as well as cognitive functions (Mori et al, 2016 ).…”
Section: Therapeutic Effects Of Dbs On Fog and The Accompanied Cognitmentioning
confidence: 99%